The journey of demand responsive transportation: Towards sustainable services - Deka, Utpal; Varshini, Vetha; Dilip, Deepthi Mary (Frontiers in Built Environment, 2023)
The concept of Demand Responsive Transport (DRT) describes a technology-enabled shared mobility service that has a flexible operating schedule and/or provides virtual stops and/or flexible routes. While these on-demand services are not new, the developments in communication and tracking technology (vehicle positioning systems) have revived these services in the past decade. The benefits of adopting DRT services for intra-community and FLM travel needs are widely accepted, but there is still a cautious approach towards their implementation due to the failure of many promising DRT schemes in the past. This article (1) creates an overview of the various on-demand services introduced across the world, to understand the factors that may have contributed to the failure of these services in the past (2) identifies the progress made towards sustainable DRT ventures through analysis of global case studies (3) provides an overview of the flexibility of vehicle and deployment technologies in the DRT sphere. A bibliometric analysis, where the top keywords were further categorised using VOSviewer's default clustering algorithm, highlighted the importance of sustainability in DRT ventures. By the progress made towards sustainable DRT ventures, it can be concluded that environmentally sustainable DRT ventures can be achieved through the adoption of electric and autonomous vehicles for DRT services, by reducing mileage of the vehicle and/or adjusting the length of route. The study concludes by reviewing existing research gaps regarding performance expectation, and recommending policy and practice implications, based on the case study of the Bus-on-Demand in Dubai, UAE.